Meta-Analysis: The Effect of Early Breastfeeding Initiation on Hypothermia and Diarrhea in Infants - Hidayah, Fristyaningrum; Retno, Yulia Lanti; Budihastuti, Uki Retno (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Early initiation of breastfeeding is the process of letting the baby instinctively breastfeed within the first hour after birth, along with skin-to-skin contact between the baby and the mother's skin which can prevent hypothermia in the baby. This study aims to analyze the relationship between early initiation of breastfeeding and the incidence of hypothermia in infants. Subjects and Method: This is a systematic review and meta-analysis study. Population= Infants aged 0-59 months, Intervention= early initiation of breastfeeding, Comparison= no early initiation of breastfeeding, Outcomes= incidence of hypothermia and diarrhea. Article searched through journal databases include: PubMed, Science Direct, Google Scholar, research gate, and Springerlink. The keywords used are breastfeeding